JPEG Pleno: Providing representation interoperability for holographic applications and devices - Schelkens, Peter; Ebrahimi, Touradj; Gilles, Antonin; Gioia, Patrick; Oh, Kwan‐Jung; Pereira, Fernando; Perra, Cristian; Pinheiro, Antonio M. G. (ETRI journal, 2019)
Guaranteeing interoperability between devices and applications is the core role of standards organizations. Since its first JPEG standard in 1992, the Joint Photographic Experts Group (JPEG) has published several image coding standards that have been successful in a plethora of imaging markets. Recently, these markets have become subject to potentially disruptive innovations owing to the rise of new imaging modalities such as light fields, point clouds, and holography. These so‐called plenoptic modalities hold the promise of facilitating a more efficient and complete representation of 3D scenes when compared to classic 2D modalities. However, due to the heterogeneity of plenoptic products that will hit the market, serious interoperability concerns have arisen. In this paper, we particularly focus on the holographic modality and outline how the JPEG committee has addressed these tremendous challenges. We discuss the main use cases and provide a preliminary list of requirements. In addition, based on the discussion of real‐valued and complex data representations, we elaborate on potential coding technologies that range from approaches utilizing classical 2D coding technologies to holographic content‐aware coding solutions. Finally, we address the problem of visual quality assessment of holographic data covering both visual quality metrics and subjective assessment methodologies.